The Role of Social Priming on the Perception of Social Touch and Impression Formation - Biancardi, Beatrice; Chaby, Laurence (2024 12th International Conference on Affective Computing and Intelligent Interaction Workshops and Demos (ACIIW), 2024)
We present a perceptual study on the influence of social context on impression formation via the judgement of social touch videos. Using the Scrambled Sentence Task to induce a context with or without reference to touch (positive, negative or neutral valence), followed by the evaluation of social touch videos, we examine how priming modifies the perception of touch and impressions about the initiator of contact. Results confirm that the social priming affected the perception of the social touch stimuli, on both the valence and intensity of the touch, as well as the impression of the person initiating the touch. An interesting interaction between the manipulated variables emerged. This study marks the first step towards integrating social touch into the modelling of the first moments of an interaction between users and virtual agents,